Notary Negligence and Legal Consequences in Unlisted Heirs Cases: Lessons from Tegal Court - Simatupang, Alan Yohansyah; Hamid, Adnan; Deni, Fitra (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study is motivated by the emergence of legal issues in notarial practice concerning the issuance of a Certificate of Inheritance Rights (SKHW) that fails to include all lawful heirs, potentially leading to disputes and diminishing public trust in the notarial profession. The objective of this research is to analyze the legal liability of notaries for such negligence based on the provisions of the Civil Code (KUHPerdata) and the Notary Law (UUJN), as well as to examine the legal consequences and validity of the deed through an analysis of the Tegal District Court Decision Number 9/Pdt.G/2021/PN.Tgl. The study employs a normative juridical method with statutory and case approaches. The findings reveal that an SKHW excluding certain heirs remains formally valid but is materially defective and may be annulled by a court ruling. It is concluded that notaries bear limited formal liability but are nonetheless obliged to uphold the principle of prudence to ensure the substantive truth of the deed.